2021
DOI: 10.3390/catal11060753
|View full text |Cite
|
Sign up to set email alerts
|

Shape Effects of Ceria Nanoparticles on the Water‒Gas Shift Performance of CuOx/CeO2 Catalysts

Abstract: The copper–ceria (CuOx/CeO2) system has been extensively investigated in several catalytic processes, given its distinctive properties and considerable low cost compared to noble metal-based catalysts. The fine-tuning of key parameters, e.g., the particle size and shape of individual counterparts, can significantly affect the physicochemical properties and subsequently the catalytic performance of the binary oxide. To this end, the present work focuses on the morphology effects of ceria nanoparticles, i.e., na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Cu/CeO 2 catalysts have recently received increasing attention, showing good conversions in low-temperature (LT-)­WGS. , According to literature reports, the catalytic activity increases with the Cu loading; , therefore, most studies have focused on highly loaded catalysts. ,, However, normalized to the Cu content, the low-loaded catalysts show higher conversions . Nevertheless, there are no detailed mechanistic studies on the loading dependence of the mechanism itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu/CeO 2 catalysts have recently received increasing attention, showing good conversions in low-temperature (LT-)­WGS. , According to literature reports, the catalytic activity increases with the Cu loading; , therefore, most studies have focused on highly loaded catalysts. ,, However, normalized to the Cu content, the low-loaded catalysts show higher conversions . Nevertheless, there are no detailed mechanistic studies on the loading dependence of the mechanism itself.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, theoretical studies have revealed a dependence on the strength of the interaction of Cu with the low-index surface facets, 34,46 which is also reflected in the catalytic activity. 29,[32][33][34]47 For 5 wt % Cu/CeO 2 catalysts, octahedra were found to exhibit the highest WGS activity at ≥200 °C, followed by rods and cubes, by providing the best Cu dispersion, the largest amount of moderately active copper oxide, and the strongest Cu−support interaction. 29 To summarize previous literature findings, the state of copper when supported by ceria strongly depends on the copper loading, and so far a major focus has been placed on highly loaded catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…These obtained values are smaller than the pure CeO x 's. 58,59 The lower E g is highly connected with the crystalline phase displacements and oxygen vacancy positions. 60,61 A small E g enables the movement of abundant O Lat at the catalyst's surface, increasing the catalytic activity.…”
Section: Optical Propertiesmentioning
confidence: 79%
“…Hence, particular efforts have been lately devoted to the rational design of CeO 2 -based oxides for WGS by fine-tuning the local surface structure and metal-ceria interactions by means of the aforementioned optimization strategies. In this perspective, the key role of ceria morphology on redox properties and metal-support interactions was disclosed over various CeO 2 -based transition metals [114][115][116]. For instance, the addition of CuO over ceria carriers of different morphology (nanorods (NR), nanocubes (NC), nanopolyhedra (NP)) affects the reducibility to a different extent, following the order NR > NP > NC [114].…”
Section: Water Gas-shift (Wgs) and Preferential Oxidation Of Co (Co-p...mentioning
confidence: 99%